Концепт вічного повернення у філософії Фрідріха Ніцше - Сінельнікова, Марія; Sinelnikova, Maria (Видавництво Львівської політехніки, 2019)
Досліджено концепт вічного повернення, який є суттю філософії Ніцше. Простежено зв’язок цього концепту з іншими ніцшеанськими ідеями, такими як воля до влади, надлюдина, «смерть» Бога та нігілізм. Наголошено, що у вічному поверненні експлікуються різноманітні аспекти, які потрібно розглядати лише в синтезі, інакше це призведе до догматизації або релятивізації вчення. Завдяки методу компаративістики та аналітики зроблено висновок, що ідея вічного повернення була продумана Ніцше не до кінця, що в подальшому викликало цілу низку різноманітних інтерпретацій, які лише ускладнили адекватне її сприйняття.

The article explores the eternal return, one of the fundamental and at the same time least clarified concepts of Nietzsche's philosophy. For this reason, in the future, the idea of eternal return has caused a great variety and sometimes questionable interpretations. And how much in these interpretations Nietzsche himself remains difficult to say. It is emphasized that the idea of eternal return explicates cosmological, anthropological, ontological, axiological, existential and metaphysical aspects. It is noted that the ontological interpretation of eternal return is about revealing the fundamental laws of the universe, that is, this concept is defined as a way of being of all things. From a cosmological point of view, eternal return implies a return of the past and the future; more precisely, in Nietzsche, they merge into one, as time is perceived by the philosopher as cyclical, and the moment seems to be frozen forever. The anthropological aspect of eternal return is usually interpreted as the possibility of human formation, the possibility of its self-transcendence, and even self-overcoming. Whereas, in existential terms, the Nietzschean concept gives the person a whole new imperative of existence, namely, to invite one to live every moment of life so that he desires his constant return. In the metaphysical sense, the value of the concept of eternal return lies primarily in the fact that it is capable of supplying the person face-to-face with metaphysical realities, colliding with them, transforming himself and everything around him, opening completely different perspectives and dimensions of being, giving them entirely new content. And, finally, in the axiological sense, eternal return forces one to become a measure of all things again, allowing it to place new values. It is emphasized that these aspects need only be considered in synthesis; otherwise it will lead to the dogmatization or relativization of Nietzschean teaching. The article uses the method of logical and historical, discursive, intertextual and categorical analysis, comparativism, analogy and scientific objectivity.
The concept of eternal recurrence in the philosophy of Fridrich Nietzsche
Keywords: Фрідріх Ніцше; вічне повернення; самоперевершення; воля до влади; надлюдина; Fridrich Nietzsche; eternal recurrence; self-overcoming; will to power; superman; 16; 165.7